الأحداث الكونية في سورة التكوير من منظور التفسير الشرعي والتفسير العلمي: دراسة موضوعية - أبو عرب، هبة الله بنت صادق بن سعيد (جامعة الأزهر - كلية الدراسات الإسلامية والعربية للبنات بدمنهور, 2020)
يهدف هذا البحث: إلى بيان المفهوم الاصطلاحي للتفسير الشرعي، والتفسير العلمي، وبيان أهمية التفريق بينهما، وعلاقة بعضهما ببعض. كما أنه يهدف بصورة رئيسية إلى دراسة أبرز أهوال القيامة في سورة التكوير، والمتمثلة بالأحدث الكونية العظيمة التي ستحدث، مما سيشاهده الناس، أو ما سيحدث بعد خراب الأرض، وانكدار والشمس والنجوم، من خلال المنظور الشرعي، والعلم التجريبي، وبيان مذاهب المتقدمين من المفسرين - ومن وافقهم إلى وقتنا الحاضر، والمعاصرين من الباحثين -فيما يسمى- بالتفسير العلمي للقرآن الكريم، في تفسير هذه الأحداث الكونية. وكذلك إيضاح مواضع الاتفاق، والاختلاف بينهما، والإشارة إلى مواضع القصور في المنهج العلمي الحديث المستعمل في تفسير هذه الآيات الكونية، وانعكاساته، وأسباب خروجه عن مقتضى التفسير الشرعي.
This research aims: to clarify the idiomatic concept of legitimate interpretation and scientific interpretation, as well as to clarify the importance of differentiating between them and the relationship between them. In addition, it aims mainly to study the most prominent horrors of the Resurrection in Surah At-Takwir, represented by the great cosmic events that will take place, from what people will see, or what will happen after the destruction of the earth and the decline of the sun and the stars, through the legitimate perspective, empirical science. As well as, it aims to clarify the doctrines of the former exegetes - and those who agree with them until the present time, and contemporary researchers - in what is called - the scientific interpretation of the Holy Qur’an, in the interpretation of these cosmic events. As well as, it aims to clarify the points of agreement and difference between them and to point to the deficiencies in the modern scientific method used in the interpretation of these cosmic verses, its implications and the reasons for its deviation from the legitimate interpretation requirement.
Keywords: علوم القرآن -- التفسير الشرعي -- التفسير العلمي -- الأحداث الكونية -- سورة التكوير